Analisis Keberhasilan Kebijakan dan Pemberdayaan Masyarakat dalam Pelaksanaan Pengelolaan Sampah Di Kabupaten Banyumas - Dimas Purbo Pambudi; Neneng Sobibatu Rohmah; Khairurrizqo Khairurrizqo; Titi Rahmawati; Muhammad Riyan Fitria Ramdlani Ramdlani (LP2M, 2025)
The problem and handling of waste in Banyumas Regency has changed. Waste became one of the problems that was not handled properly in 2018 to the point of a waste emergency, but now waste in Banyumas can be a source of income, empower the community and become a model for waste management in Indonesia and even the world to achieve various achievements due to its successful management. The existence of Regent Regulation No. 24 of 2023 on the Implementation of Waste Management is a tangible manifestation of Banyumas' strong commitment in dealing with the waste problem to achieve various national and international awards for its success in waste management and care for environmental sustainability. The purpose of this paper is to describe, explore and analyze the success of policy innovation and community empowerment in the idea of “Sumpah Beruang (turning waste into money)”. This research method is descriptive qualitative by using literature studies to obtain various credible data. The results showed that the success of policy innovation and community empowerment in waste management in Banyumas can be seen in its implementation, starting from the government's commitment in the form of clear rules, budget commitments, cooperation and the use of technology. In addition, community participation is also very good in managing waste at TPST (Integrated Waste Processing Site) and TPA BLE (Environmental and Education-Based Final Processing Site) as the key to successful waste management. Finally, the thing that makes a difference in handling waste is the application of circular economy principles that can utilize the processed waste into various objects of economic value such as compost production, paving, magot cultivation, and produce staples for RDF (Refused Derived Fuel). Keywords: Policy Success, Community Empowerment, Waste Management